Application of L-theanine and L-theanine composite material in preparation of products for preventing and treating dentin hypersensitivity
By promoting the closure of dentinal tubules and inhibiting the transmission of nerve excitability through L-theanine and its composite materials, the long cycle and safety risk problems of existing dentin hypersensitivity treatment are solved, and a safe and effective dentin hypersensitivity treatment plan is provided.
Patent Information
- Application Number
- CN202510923437.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-09-19
Smart Images

Figure CN120661493A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedicine technology, and particularly relates to the application of L-theanine and a composite material thereof in the preparation of products for preventing and treating dentin hypersensitivity. Background Art
[0002] Dentin hypersensitivity is a very common condition in dental clinics. Its main manifestation is the rapid onset of sharp local or systemic pain when exposed to external stimuli, which seriously affects the patient's quality of life, especially causing significant inconvenience in eating, cleaning teeth, and daily activities. Without timely intervention, symptoms may continue to worsen, eventually leading to enamel wear, gingival recession, and even irreversible tooth damage. Existing treatment strategies for dentin hypersensitivity are mainly based on two principles: mineralization and closure of dentinal tubules and reduction of pulp nerve excitability. Mineralization and closure of dentinal tubules aims to block exposed dentinal tubule openings, physically isolating the conduction of stimuli. However, this method has a long treatment cycle and poor sealing effect, requiring patients to return for multiple follow-up visits for maintenance treatment. Reduction of pulp nerve excitability is achieved by reducing the sensitivity of the pulp nerve to stimuli or blocking the conduction pathway. Compared with tubule closure, its effect lasts shorter. However, new biomaterials used to reduce pulp nerve excitability often rely on complex chemical synthesis and artificial modification processes, which not only increases production costs and the difficulty of clinical translation, but also introduces potential risks of biocompatibility and adverse reactions.
[0003] Due to the aforementioned limitations and the diversity of treatment methods and evaluation systems, the industry has yet to establish a "gold standard" for the treatment of dentin hypersensitivity. Exploring more rational, effective, and safe treatment options is urgently needed. Consequently, research in this field is rapidly developing toward the synergistic effects of multiple mechanisms, innovative active ingredients, and upgraded evaluation systems.
[0004] Traditional Chinese medicine (TCM) is a treasure trove of naturally active ingredients. Leveraging modern scientific methods to further explore the active ingredients of Chinese herbal medicines for the prevention and treatment of oral diseases, particularly addressing issues such as dentin hypersensitivity where existing treatments are ineffective, not only has significant clinical value but also represents a key avenue for promoting the modernization of TCM. Summary of the Invention
[0005] The object of the present invention is to provide an application of L-theanine and a composite material thereof in the preparation of a product for preventing and treating dentin hypersensitivity.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: The first aspect of the present invention discloses the use of L-theanine and a composite material thereof in the preparation of a product for preventing and treating dentin hypersensitivity.
[0007] In some embodiments of the present invention, the composite material is L-theanine-loaded hollow mesoporous silica L-theanine / CaO2@HMS.
[0008] In some embodiments of the present invention, the preparation method of L-theanine / CaO2@HMS comprises the following steps: S1. Dispersing hollow mesoporous silica nanoparticles in an L-theanine solution, reacting, centrifuging, collecting the precipitate, washing, and freeze-drying to obtain the L-theanine@HMS composite material; S2. The composite material L-theanine@HMS was reacted with calcium peroxide in an organic solvent, followed by centrifugation. The precipitate was collected, washed, and freeze-dried to obtain L-theanine-loaded hollow mesoporous silica L-theanine / CaO2@HMS.
[0009] In some embodiments of the present invention, in step S1, the concentration of the L-theanine solution is 10-40 mM, preferably 20 mM; the ratio of the L-theanine solution to the hollow mesoporous silica nanoparticles is 5-20 mL:25-100 mg, preferably 10 mL:50 mg; Preferably, the hollow mesoporous silica nanoparticles are dispersed in the L-theanine solution, stirred at room temperature for 6 to 24 hours, preferably 12 hours, and then reacted in the dark for 6 to 24 hours, preferably 12 hours.
[0010] In some embodiments of the present invention, in step S2, the organic solvent is anhydrous ethanol; The mass ratio of L-theanine@HMS to calcium peroxide is 1:0.5~2, preferably 1:1; In step S2, the reaction is stirred at room temperature in the dark for 12 to 48 hours, preferably 24 hours.
[0011] In some embodiments of the present invention, the hollow mesoporous silica nanoparticles are prepared by a hard template method and a selective etching method. The preparation method of the hollow mesoporous silica nanoparticles is an existing technology.
[0012] In some embodiments of the present invention, the preparation method of hollow mesoporous silica nanoparticles is as follows: adding an ethanol solution of ethyl orthosilicate dropwise to an ethanol-ammonia mixed solution, reacting at room temperature for 0.5 to 2 hours, centrifuging, collecting the precipitate, washing, and drying to obtain a SiO2 nanoparticle template; The SiO2 nanoparticle template is dispersed in water to obtain a SiO2 nanoparticle suspension; the suspension is slowly added to a cetyltrimethylammonium bromide (CTAB) solution and reacted at room temperature for 10 to 60 minutes, and then a mixture of ethyl orthosilicate and ethanol is added to the system, and the reaction is continued by stirring at room temperature for 3 to 12 hours; after the reaction is completed, the product is collected by centrifugation and redispersed in deionized water, and then sodium carbonate is added and heated for reaction; the reaction product is collected by centrifugation and washed to finally obtain SiO2 nanoparticles with a hollow structure.
[0013] The ethanol-ammonia aqueous solution is prepared by mixing 8-12 mL of deionized water, 65-75 mL of anhydrous ethanol, and 1-2 mL of ammonia aqueous solution.
[0014] Take another 2 mL of ethyl orthosilicate and dissolve it in 1-4 mL of anhydrous ethanol by ultrasonication to prepare an ethanol solution of ethyl orthosilicate.
[0015] The volume ratio of the ethanol solution of ethyl orthosilicate to the ethanol-ammonia aqueous solution is 1:15~40.
[0016] The concentration of SiO2 nanoparticle suspension was 2–10 mg / mL; The preparation method of cetyltrimethylammonium bromide (CTAB) solution is as follows: 10-20 mL of deionized water, 10-20 mL of anhydrous ethanol, and 0.1-0.4 mL of ammonia water are mixed uniformly; 35-150 mg of cetyltrimethylammonium bromide (CTAB) is weighed and added to the mixture, and ultrasonic treatment is performed to completely dissolve it to prepare a CTAB solution.
[0017] The volume ratio of SiO2 nanoparticle suspension to CTAB solution is 1:0.5~2.
[0018] SiO2 nanoparticle suspension and ethyl orthosilicate ethanol solution 40~160:1.
[0019] Preferably, the mass of sodium carbonate is 4 to 16 times that of the SiO2 nanoparticle template.
[0020] Preferably, after adding sodium carbonate, stirring is carried out at 40-60° C., more preferably 50° C., for 1-4 hours to achieve selective etching of the SiO 2 nanoparticle template.
[0021] In some embodiments of the present invention, the preparation of SiO2 nanoparticles further includes a purification step: dispersing the etched SiO2 nanoparticles into a mixed solution containing ethanol and hydrochloric acid, heating under reflux to completely remove residual CTAB, then washing alternately with deionized water and anhydrous ethanol, and freeze-drying to obtain hollow mesoporous silica. The mixed solution of ethanol and hydrochloric acid contains a volume ratio of ethanol to hydrochloric acid of 5 to 20:1. Preferably, heating under reflux at 70 to 90°C for 6 to 24 hours.
[0022] The second aspect of the present invention discloses a product for preventing and treating dentin hypersensitivity, which comprises L-theanine and / or a composite material thereof and a pharmaceutically acceptable carrier.
[0023] The third aspect of the present invention discloses a product for preventing and treating dentin sensitivity, which comprises a medical device with a coating on the surface; the coating comprises L-theanine and / or a composite material thereof.
[0024] Compared with the prior art, the present invention has the following beneficial effects: The invention is scientifically designed and ingeniously conceived, and for the first time discovers that L-theanine has the effects of mineralizing and sealing dentinal tubules and reducing the excitability of dental pulp nerves, and is used for preventing and treating dentine hypersensitivity, with a precise effect.
[0025] The present invention discovered that L-theanine can effectively promote the biomimetic mineralization of collagen fibers and demineralized dentin sheets, thereby significantly sealing dentinal tubules. Furthermore, L-theanine competitively antagonizes the excitatory neurotransmitter glutamate at glutamate receptors, effectively inhibiting the transmission of excitatory nerve signals and achieving a significant analgesic effect.
[0026] The L-theanine composite material L-theanine / CaO2@HMS of the present invention uses the oxygen-producing ability of CaO2 as a driving force to better transport L-theanine into the dentinal tubules and release L-theanine, thereby promoting deep sealing of the tubules and improving the therapeutic effect of dentin hypersensitivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a diagram showing the effect of L-theanine in promoting collagen mineralization. From left to right, each group includes a transmission electron microscope image of mineralized collagen, a diffraction result image, a Ca element distribution image, a P element distribution image, a N element distribution image, and an O element distribution image.
[0028] Figure 2 These are scanning electron micrographs of mineralized dentin; from left to right, each group is a scanning electron micrograph of the surface morphology of mineralized dentin, a partial magnified view of the surface morphology, a scanning electron micrograph of the cross-sectional morphology of mineralized dentin, and a partial magnified view of the cross-sectional morphology.
[0029] Figure 3Surface plasmon resonance results; from left to right: L-theanine binding to glutamate receptor results; glutamate binding to glutamate receptor results; glutamate binding to glutamate receptor in the presence of L-theanine.
[0030] Figure 4 Figure 3 is the docking result of L-theanine and glutamate receptor molecules, where a is the position of the L-theanine molecule in the three-dimensional structure of the glutamate receptor protein; b is the two-dimensional binding mode of the L-theanine molecule and the glutamate receptor protein, with the green dotted line indicating hydrogen bonding and the red gear shape indicating hydrophobic interaction; c is the three-dimensional binding mode of theanine molecule (L-theanine) and mGluR5 (glutamate receptor), with the green dotted line indicating hydrogen bonding; Ligand represents ligand, Binding Energy (kcal / mol) represents binding energy, and Predicted Ki represents the predicted inhibition constant.
[0031] Figure 5 These are the morphologies of L-theanine composite materials. The first row, from left to right, are the scanning electron microscope morphology of L-theanine / CaO2@HMS, Si element distribution map, and O element distribution map; the second row, from left to right, are the C element distribution map, N element distribution map, and Ca element distribution map.
[0032] Figure 6 This is the EDS result of the L-theanine composite material (L-theanine / CaO2@HMS); Spectra from area #1 Spectrum represents the spectrum in area 1; the horizontal axis Energy (keV) represents the energy (keV), and the vertical axis Intensity (kcounts) represents the intensity (kilocounts).
[0033] Figure 7 This is a graph showing the Zeta potential investigation results of hollow mesoporous silica (HMS), HMS composite material loaded with L-theanine (L-theanine@HMS), and L-theanine composite material (L-theanine / CaO2@HMS); the vertical axis Zetapotential (mV) represents the Zeta potential (mV).
[0034] Figure 8 The infrared spectra of calcium peroxide, hollow mesoporous silica (HMS), HMS composite material loaded with L-theanine (L-theanine@HMS) and L-theanine composite material (L-theanine / CaO2@HMS); the horizontal axis Wavenumber (cm -1 ) represents the wave number (cm -1), the vertical axis Transimittance (%) represents the transmittance (%).
[0035] Figure 9 This is the result of investigating the L-theanine release of the L-theanine composite material (L-theanine / CaO2@HMS); the horizontal axis Time (days) represents time (days), the vertical axis Transimittance (%) represents transmittance (%); the vertical axis L-theanine cumulative release (mM) represents the L-theanine release amount (mM).
[0036] Figure 10 This is the oxygen release investigation result of L-theanine composite material (L-theanine / CaO2@HMS); the horizontal axis Time (min) represents time (minutes), and the vertical axis Dissolved O2 (mg / L) represents the oxygen release amount.
[0037] Figure 11 This is a graph showing the results of the biosafety investigation of L-theanine; the horizontal axis "Time" represents time, and the vertical axis "CellViability(%)" represents cell viability (%). DETAILED DESCRIPTION
[0038] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.
[0039] The L-theanine in the examples of the present invention was provided by Shanghai MacLean Biochemical Technology Co., Ltd. (Cat. No. L819048).
[0040] Example 1 This example investigates the sealing effect of L-theanine on dentinal tubules by regulating collagen mineralization and dentin mineralization. 1. Study on the role of L-theanine in regulating collagen mineralization Prepare collagen stock solution: Dissolve commercial type I collagen in 0.1 M acetic acid to a concentration of 3 mg / mL. Store at 4°C until ready for use.
[0041] Prepare the assembly solution: The assembly solution consists of 50 mM glycine and 200 mM KCl. Adjust the pH to 9.2 using an appropriate concentration of KOH or NaOH solution. Prepare and use immediately.
[0042] Prepare recombinant collagen solution: Add 16.7 μL of collagen stock solution to 983.3 μL of assembly solution, immediately vortex to mix, and incubate at room temperature for 20 min to a final concentration of 50 μg / mL. After incubation, the recombinant collagen should show slight gelation with no fiber precipitation.
[0043] To load recombinant collagen onto nickel meshes, place the nickel meshes face-up on the wax sheet at the bottom of a six-well plate. Add 14 μL of recombinant collagen solution to each mesh. Add ultrapure water (DIW) to the remaining wells to maintain a moist environment. Seal the plate with parafilm and incubate at 37°C for 24 hours. After incubation, rinse the nickel meshes three times with DIW. Fix the rinsed meshes in 0.5 wt% glutaraldehyde solution for 2 hours, remove them, rinse them again with DIW, and air-dry them. This results in the recombinant collagen-loaded nickel meshes, which are then ready for use.
[0044] Prepare a mineralization solution containing L-theanine: Dissolve L-theanine in deionized water. Add 5 mL of CaCl₂ solution and mix thoroughly. Then, dropwise add 10 mL of Na₂HPO₄ solution and mix again. The final mineralization solution composition is: 1.67 mM CaCl₂, 4.75 mM Na₂HPO₄, and 25 mM L-theanine. Prepare this mineralization solution immediately and sterile filter it before use.
[0045] The composition of the mineralization solution without L-theanine is: 1.67 mM CaCl2, 4.75 mM Na2HPO4.
[0046] Grouping: Nickel mesh loaded with recombinant collagen was randomly divided into an L-theanine group and a control group without L-theanine. The two groups of nickel mesh were placed in separate wells of a six-well plate. The control group was treated with a mineralization solution without L-theanine, while the L-theanine group was treated with a mineralization solution containing L-theanine, ensuring that the surface of the nickel mesh was completely covered.
[0047] Collagen mineralization was observed using TEM. After one day of mineralization, two nickel grids were randomly removed from each group, rinsed with DIW, and air-dried. The collagen mineralization was then observed under TEM, and images of representative areas were taken. SAED analysis was also performed, and EDS surface scanning was used to determine the elemental distribution of the mineralized collagen.
[0048] The results are as follows Figure 1 As shown. Figure 1 As can be seen, the collagen in the control group showed a low-density, fuzzy image due to the lack of intrafibril mineralization, with a small number of crystals outside the collagen and no diffraction rings in the SAED image. In contrast, the collagen density in the theanine group increased, with scattered crystals outside the collagen fibers, diffraction rings appearing in the SAED image, and calcium and phosphorus distributed along the collagen fibers, suggesting intra- and extra-fibrillary mineralization.
[0049] 2. Study on the role of L-theanine in regulating dentin mineralization The extracted teeth were used within 2 weeks of extraction. First, a hard tissue slicer was used to cut a dentin slice approximately 1 mm thick from the middle of the crown parallel to the occlusal plane. During cutting, it was necessary to ensure that the direction of the dentinal tubules was perpendicular to the subsequent processing surface (i.e., the slice plane). Subsequently, the dentin samples were finely polished using silicon carbide sandpaper of increasing mesh size (1200 mesh, 2000 mesh, and 3000 mesh, respectively) under running water cooling. The dentin samples were immersed in a 37% phosphoric acid solution and etched for 30 seconds. After the etching treatment, all samples were ultrasonically cleaned again with deionized water for 10 minutes. The processed dentin samples could be used for subsequent experiments.
[0050] Grouping: Dentin samples following the acid-etching and cleaning treatment were randomly divided into two groups: an L-theanine group and a control group without L-theanine. Samples in the control group were mineralized in a mineralization solution containing only the basic mineralizing components (1.67 mM CaCl₂, 4.75 mM Na₂HPO₄), while samples in the L-theanine group were mineralized in a mineralization solution containing L-theanine. All samples were placed in a six-well plate, ensuring that the mineralization solution completely submerged the samples. The plates were sealed with parafilm and incubated in a 37°C oven. Dentin samples were randomly removed from each group on the third and seventh days of incubation for further examination.
[0051] Samples were randomly selected before and after demineralization, as well as after mineralization at different time points within each group, and surface morphology changes were observed using scanning electron microscopy (SEM). After ultrasonic cleaning for 20 minutes, the samples were dehydrated in a gradient of ethanol (volume fractions: 30%, 50%, 70%, 90%, and 100%). Following dehydration, they were fixed in hexamethyldisilane for an additional 2 hours and then placed in a fume hood overnight. After gold spraying in a vacuum environment for 30 seconds, the samples were observed using a scanning electron microscope at an accelerating voltage of 20 keV.
[0052] The results are as follows Figure 2 As shown. Figure 2 It can be seen that with the extension of mineralization time, spherical crystals appeared on the surface of dentin in the control group, covering the area around the dentinal tubules, failing to enter the interior of the dentinal tubules, and unable to completely cover the exposed dentinal tubules; while flake crystals appeared on the surface of dentin in the theanine group, entering the interior of the dentinal tubules to a depth of about 20μm, and better covering the dentinal tubules.
[0053] Example 2 This example discloses an experiment to study the effect of L-theanine on inhibiting nerve excitability transmission.
[0054] 1. Investigation of the affinity of L-theanine for glutamate receptors 1.1 Protein coupling: (1) Place the running buffer (200 mL 1× PBS Buffer), water bottle, and waste liquid bottle in the left and right trays respectively, and insert the corresponding liquid inlet tubes.
[0055] (2) Hold the CM5 chip with the printed side facing up. Gently push the chip into the card slot in the direction of the arrow on the chip, and then close the chip compartment door.
[0056] (3) Activate channel 4 of the chip with 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC, Cytiva) and N-hydroxysuccinimide (NHS, Cytiva) at a flow rate of 10 μL / min.
[0057] (4) The ligand protein was diluted to 50 μg / mL with sodium acetate, and mGluR5 was fixed to channel 4 of the chip at a flow rate of 10 μL / min to generate a coupling map.
[0058] (5) The channel was blocked with ethanolamine at a flow rate of 10 μL / min.
[0059] (6) Repeat steps (3)-(5) for channel 3 as a reference, except that protein-free acetate buffer is used in step (4).
[0060] 1.2 Protein-small molecule interaction test: (1) Solvent correction (dimethyl sulfoxide, DMSO) For small molecules, use the interaction buffer as the running buffer. Replace the original running buffer in the tray on the left side of the system with the interaction buffer and insert the corresponding inlet tube. Prepare a 5% DMSO concentration calibration curve by mixing 4.5% and 5.8% stock solutions according to the table below: Table 1 Solvent calibration solution preparation table
[0061] (2) Small molecule assay Each small molecule was diluted to several concentrations in a 96-well plate, and the interaction buffer was run through the chip, coupling with the target protein from low to high concentrations. The flow rate was 30 μL / min, and the duration was 60 s. After each concentration point, the chip was regenerated with 10 mM glycine hydrochloride (pH 2.0) for 5 minutes. This process was repeated until all the corresponding small molecule concentrations were run. The data were globally fitted to a 1:1 Langmuir binding model to obtain association and dissociation constants.
[0062] The results are as follows Figure 3 As shown. Figure 3It can be seen that both L-theanine and glutamate can bind to mGluR5 in a dose-dependent manner. D is 4.96 μM, and the K of glutamate D was 2.47 μM, which was higher than that of theanine. However, in the presence of L-theanine, the K D The concentration of L-theanine increased to 57.4 μM, and Rmax (maximum response value) remained unchanged, indicating that L-theanine and glutamate have a competitive inhibitory effect on mGluR5. Based on the role of glutamate and glutamate receptors in nerve excitability transmission, L-theanine can act as a glutamate analog and glutamate receptor antagonist, competitively binding to glutamate receptors, interfering with the binding of glutamate to glutamate receptors, and thus alleviating the pain symptoms caused by dentin hypersensitivity.
[0063] 2. Mechanism of L-theanine and glutamate receptors The three-dimensional structure of the glutamate receptor protein from the Uniprot database (Uniprot ID: P41594) was used as the initial structure for subsequent molecular docking. This initial structure was processed using AutoDock Tools 1.5.6, preserving the protein's original charge and generating a pdbqt file for subsequent molecular docking.
[0064] The L-theanine structure was downloaded from the PubChem website. The MOPAC program was then used to optimize the molecular structure and calculate the PM3 atomic charges for subsequent molecular docking. The ligand structure was processed using AutoDock Tools 1.5.6 to generate a pdbqt file for docking.
[0065] Molecular docking was implemented using the AutoDock Vina software package. The center coordinates of the docking box were set to the center of the protein to enclose the entire protein structure. The number of grid points in each XYZ direction was set to 100 × 100 × 100, the grid size was 0.500 Å, the number of dockings was set to 50, and the rest of the parameters used the default values.
[0066] Molecular docking results may result in unreasonable atomic contacts in the spatial structure. Energy optimization can be used to release these forces and stabilize the structure. Energy optimization uses the Amber14 force field. The optimization process is divided into two steps: first, a 1000-step steepest descent optimization method, followed by a 5000-step conjugate gradient method to further optimize the structure. The final result is used as the model for subsequent analysis.
[0067] The results are as follows Figure 4 As shown. Figure 4L-theanine molecules can be found to stably bind to the cavity of the glutamate receptor protein, which is composed of amino acids Val60, Glu62, Gln63, Arg362, His391, and Val392. Further analysis of the interactions between the two molecules revealed that hydrophobic interactions and hydrogen bonds form between the L-theanine molecule and the surrounding amino acids, promoting stable binding to the glutamate receptor protein. Specifically, three hydrogen bonds are formed between the L-theanine molecule and the Glu62 and Val392 amino acids surrounding the glutamate receptor protein. Furthermore, hydrophobic interactions are formed between the L-theanine molecule and the four amino acids surrounding the glutamate receptor pocket, further enhancing the affinity of the L-theanine molecule for the glutamate receptor protein. The binding energy between the L-theanine molecule and the glutamate receptor protein, predicted by Autodock vina software, is -5.634 kcal / mol. This strong binding energy indicates that the L-theanine molecule is stably bound to the glutamate receptor protein.
[0068] Example 3 This example discloses an experimental study on the effect of L-theanine composite materials on treating dentin hypersensitivity.
[0069] 1. Synthesis of Hollow Mesoporous Silica (HMS) (Support) Hollow mesoporous silica nanoparticles (HMS) were prepared by hard template method and selective etching method. Preparation of SiO2 nanoparticle templates: 10 mL of deionized water and 69.4 mL of anhydrous ethanol were mixed uniformly. 1.6 mL of aqueous ammonia was then added to the mixture and stirred to obtain an ethanol-ammonia mixed solution. Separately, 2 mL of tetraethyl orthosilicate (TEOS) was ultrasonically dissolved in 2 mL of anhydrous ethanol to prepare a TEOS / ethanol mixed solution. With stirring at 1000 rpm, the TEOS / ethanol mixture was slowly added dropwise to the ammonia mixed solution using a syringe pump at a flow rate of 1 mL / min. The mixture was allowed to react at room temperature for 1 hour. After the reaction, the resulting dispersion was centrifuged at 10,000 rpm for 10 minutes, and the resulting precipitate was collected. The precipitate was then washed by alternating centrifugation with deionized water and anhydrous ethanol multiple times to obtain pure SiO2 nanoparticle templates. The resulting templates were freeze-dried and stored for future use.
[0070] 50 mg of freeze-dried SiO2 nanoparticle template was weighed and added to 10 mL of deionized water. Ultrasonic dispersion was performed for 15 minutes to obtain a uniformly dispersed SiO2 nanoparticle suspension (5 mg / mL). 15 mL of deionized water, 15 mL of anhydrous ethanol, and 0.275 mL of aqueous ammonia were mixed thoroughly. 75 mg of cetyltrimethylammonium bromide (CTAB) was added to the mixture and ultrasonicated to completely dissolve it, preparing a CTAB solution. The SiO2 nanoparticle suspension was slowly added to the CTAB solution and stirred thoroughly at room temperature for 0.5 hours. Subsequently, 0.125 mL of the TEOS / ethanol mixture was added to the system using a syringe pump, and the reaction was continued by stirring at room temperature for 6 hours. After the reaction was complete, the product was collected by centrifugation and redispersed in 10 mL of deionized water. 424 mg of sodium carbonate (Na2CO3) was then added and stirred at 50°C for 2 hours to achieve selective etching of the SiO2 nanoparticle template. The reaction product was collected by centrifugation and washed alternately with deionized water and anhydrous ethanol to obtain hollow SiO2 nanoparticles. To further remove CTAB, the product was dispersed in a mixture of 70 mL of ethanol and 7 mL of hydrochloric acid and refluxed at 80°C for 12 hours to completely remove residual CTAB. Finally, the purified product was collected and washed alternately with deionized water and anhydrous ethanol to obtain HMS (hollow mesoporous silica). The product was lyophilized and stored for later use.
[0071] 2. Synthesis of L-theanine composite material (L-theanine / CaO2@HMS) L-theanine was dissolved in water to prepare a 20 mM L-theanine solution. Subsequently, 50 mg of hollow mesoporous silica was dispersed into 10 mL of L-theanine solution and reacted under continuous stirring for 12 hours. After that, it was placed in a dark environment and continued to shake for 12 hours to achieve maximum encapsulation. After encapsulation, the mixture was centrifuged, the precipitate was collected, and it was repeatedly washed with deionized water and anhydrous ethanol, and finally freeze-dried to obtain the HMS composite material L-theanine@HMS loaded with L-theanine.
[0072] 0.1 g of L-theanine@HMS was added to 15 mL of anhydrous ethanol, followed by 0.1 g of calcium peroxide (CaO2). The mixture was stirred and reacted for 24 hours at room temperature in the dark. After the reaction, the resulting white solid product was collected by centrifugation at 12,000 rpm for 10 minutes at 25°C. The solid was then quickly washed with anhydrous ethanol and then ultrapure water (ddH2O). After each wash, the solid was centrifuged and the supernatant discarded. The final product was freeze-dried to obtain L-theanine / CaO2@HMS.
[0073] 3. Characterization of L-theanine composite material (L-theanine / CaO2@HMS) 3.1 Basic characterization of L-theanine composites L-theanine / CaO2@HMS was dispersed in anhydrous ethanol, and an appropriate amount of the solution was dripped onto a nickel mesh. The samples were observed and photographed using a transmission electron microscope (200 kV), and analyzed using Fourier transform infrared spectroscopy and zeta potential analysis.
[0074] The results are as attached Figures 5 to 8 As shown. Figure 5 It can be seen that the TEM photo shows that the hollow mesoporous silica has a complete skeleton structure, and the contrast in the center is lower than that in the surrounding area. The mapping results show that C, O, Si, N, and Ca are co-localized, indicating that the material was successfully synthesized.
[0075] Depend on Figure 6 It can be seen that EDS shows that the main element components of the composite material are C, O, Si, N, and Ca.
[0076] Depend on Figure 7 Zeta potential analysis reveals changes in the potential of hollow mesoporous silica upon loading with L-theanine and CaO2. When HMS is dispersed in anhydrous ethanol, its zeta potential is -20 mV, while this increases to 1.20 mV after loading with theanine. After CaO2 loading, the zeta potential of L-theanine / CaO2@HMS is -43.6 mV.
[0077] Depend on Figure 8 It can be seen that HMS at 1068 cm -1 , 800 cm -1 and 450 cm -1 The absorption peaks near the sample are typical Si-O-Si bond absorption vibration peaks, namely the asymmetric stretching vibration peak, symmetric stretching vibration peak and bending vibration peak of Si-O-Si, indicating that the sample has a silicon-based skeleton. L-theanine@HMS superimposes 1633 cm-1 The absorption vibration peak of (C=O) indicates the successful loading of L-theanine. L-theanine / CaO2@HMS superimposes the absorption vibration peak of 873 cm -1 (OO) and 1430 cm -1 The absorption vibration peak of (O-Ca-O) indicates the successful synthesis of L-theanine / CaO2@HMS.
[0078] 3.2 L-theanine release and oxygen release of L-theanine composite materials (1) Investigation of L-theanine release 50 mg of L-theanine / CaO2@HMS was dispersed in 10 mL of phosphate buffered saline (PBS), placed in the dark, and continuously shaken at 120 rpm. Samples were taken at various predetermined time points, and the mixed solution was centrifuged at 4200 rpm for 4 minutes. 1 mL of the supernatant was collected for UV-Vis spectral analysis. After each sampling, 1 mL of fresh PBS was added to maintain a constant total volume.
[0079] The results are as attached Figure 9 As shown by Figure 9 It can be seen that the release of L-theanine is characterized by an initial rapid release during the first 1 day and a relatively slow sustained release over 1-4 days.
[0080] (2) Investigation of oxygen release The oxygen release performance of L-theanine / CaO2@HMS was tested as follows: L-theanine / CaO2@HMS was dispersed in PBS buffer. A dissolved oxygen meter probe was then inserted into the solution, and the liquid surface was covered with a layer of liquid paraffin to reduce external interference. The changes in oxygen concentration measured by the dissolved oxygen meter were recorded at various time points to evaluate the material's oxygen release behavior.
[0081] The results are as attached Figure 10 As shown by Figure 10 It can be seen that L-theanine / CaO2@HMS can stably produce O2 and drive L-theanine / CaO2@HMS into the dentinal tubules.
[0082] Example 4 This example investigates the biosafety of L-theanine. The specific steps are as follows: The cytotoxicity of theanine was evaluated using human dental pulp stem cells, and cell viability was determined using the CCK-8 assay. Different concentrations of theanine (1 μM, 10 μM, 100 μM, 1 mM, and 10 mM) were prepared. The cell suspension was seeded into a 96-well plate and incubated overnight at 37°C to allow attachment. Six replicate wells were set up for each concentration. After attachment, the cells were washed with PBS and incubated in DMEM medium containing theanine for 1, 3, and 5 days. Afterward, 10 μL of CCK-8 reagent and 90 μL of culture medium were added to each well. The absorbance at 450 nm was measured using a microplate reader, and cell viability was calculated.
[0083] The biosafety results of L-theanine are shown in the attached Figure 10 As shown by Figure 11 It can be seen that after culturing HDPCs with different concentrations of L-theanine for 1, 3, 5, and 7 days, the cell survival rate was higher than 90%, indicating that L-theanine had no obvious cytotoxicity.
[0084] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention and are intended to illustrate the technical solutions of the present invention, not to limit the present invention, and certainly not to limit the scope of the present invention. Any modifications or improvements that are insubstantial to the main design concept and spirit of the present invention, provided that the technical problems they solve are consistent with the present invention, shall be included within the scope of protection of the present invention. Furthermore, any direct or indirect application of the technical solutions of the present invention to other related technical fields shall also be included within the scope of protection of the present invention.
Claims
1. Application of L-theanine and its composite materials in the preparation of products for preventing and treating dentin hypersensitivity.
2. The use according to claim 1, characterized in that The composite material is hollow mesoporous silica L-theanine / CaO2@HMS loaded with L-theanine.
3. The use according to claim 2, characterized in that The preparation method of L-theanine / CaO2@HMS includes the following steps: S1. Dispersing hollow mesoporous silica nanoparticles in an L-theanine solution, reacting, centrifuging, collecting the precipitate, washing, and freeze-drying to obtain the L-theanine@HMS composite material; S2. The composite material L-theanine@HMS was reacted with calcium peroxide in an organic solvent, followed by centrifugation. The precipitate was collected, washed, and freeze-dried to obtain L-theanine-loaded hollow mesoporous silica L-theanine / CaO2@HMS.
4. The use according to claim 3, characterized in that In step S1, the concentration of the L-theanine solution is 10-40 mM, preferably 20 mM; the ratio of the L-theanine solution to the hollow mesoporous silica nanoparticles is 5-20 mL:25-100 mg, preferably 10 mL:50 mg; Preferably, the hollow mesoporous silica nanoparticles are dispersed in the L-theanine solution, stirred at room temperature for 6 to 24 hours, preferably 12 hours, and then reacted in the dark for 6 to 24 hours, preferably 12 hours.
5. The use according to claim 3, characterized in that In step S2, the organic solvent is anhydrous ethanol; The mass ratio of L-theanine@HMS to calcium peroxide is 1:0.5~2, preferably 1:1; In step S2, the reaction is stirred at room temperature in the dark for 12 to 48 hours, preferably 24 hours.
6. The use according to any one of claims 3 to 5, characterized in that: Hollow mesoporous silica nanoparticles were prepared by hard template method and selective etching method.
7. A product for preventing and treating dentin hypersensitivity, characterized in that: The invention comprises L-theanine and / or a composite material thereof and a pharmaceutically acceptable carrier.
8. A product for preventing and treating dentin hypersensitivity, characterized in that: The product comprises a medical device with a coating on the surface; the coating comprises L-theanine and / or a composite material thereof.